E0388 Effect of endothelial progenitor cells from peripheral blood in patients with coronary heart disease before and after extracorporeal cardiac shock wave therapy. (17th November 2010) - Cai, H Y; Wang, Y; Li, L; Zhao, L; Yang, X Y; Xiao, J M; Cao, J M; Yang, X Y; Yang, C H; Guo, T
Abstract : Objective: To study the effects of CSWT on the proliferation, differentiation of endothelial progenitor cells (EPCs) from peripheral blood in patients with coronary heart disease (CAD). Methods: Total mononuclear cells were isolatedfrom patients with coronary heart disease (n=25) and age-matched control subjects (n=25) by Ficoll density gradient centrifugation, and then the cells were plated on fibronectin coated culture dishes. After 7 days of culture. EPCs were characterised as adherent cells double positive for DiLDL-uptake and lectin binding by direct fluorescent staining under alaser scanning confocal microscope. Results: The number and proliferation of EPCs was significantly increased in patients CSWT as compared with that in control subjects (p<0.05), CSWT could markedly promote the proliferation and the differentiation towards the endothelial cell lineage of EPCs in CAD. Conclusion: CSWT could markedly promote the proliferation and the differentiation towards the endothelial cell lineage of EPCs in CAD.